Differential investment in an AI-based technology and economic growth: a tale of two regions - Amitrajeet A. Batabyal; Hamid Beladi (Eastern Journal of European Studies, 2025)
In this paper, we analyze a dynamic model in which two stylized regions, A and B, use an artificial intelligence (AI)-based technology α(t) to produce a knowledge good Qt. Even though the initial value of the AI-based technology α(0) is identical in both regions, region A saves and hence invests more than region B to make the existing AI-based technology more powerful. We show that this differential investment means that the ratio of the output of the knowledge good in region A to region B or QAQB is continually rising. In other words, without targeted policy, region A will become a "leading region" that experiences economic growth and innovation ahead of region B which will become a "lagging region" that innovates less and hence tends to grow more slowly.